Preventive Nursing, Community Engagement, Health Promotion: The Pathway to Improving Health Care in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
The article explores the many obstacles that the Nigerian healthcare system encounters and suggests a holistic strategy that includes preventive nursing, health promotion, and community participation to improve healthcare provision. The research underscores the significance of community participation, emphasising its function in cultivating a feeling of affiliation and possession, as well as establishing a connection between the community and healthcare programmes. The text extensively examines the notion of preventative nursing, highlighting its multiple character as both a specialised nursing practice and a subject rooted in public health. The objectives and constituents of preventive nursing are delineated, highlighting its function in timely identification, proactive interventions, and its influence on national health results. Health promotion is presented as a vital component of healthcare reforms, with the goal of enabling people to make knowledgeable decisions about their well-being. The article outlines the objectives of health promotion, with a particular focus on minimising risk factors and encouraging a proactive approach to maintaining good health. The text discusses strategies for efficacious health promotion in Nigeria, including the engagement of community leaders and the use of both conventional and digital approaches. The text examines the notion of community participation, characterising it as a multifaceted and all-encompassing process that entails a dynamic interchange of ideas and resources among many stakeholders. The research highlights the significance of active community engagement in decision-making processes, emphasising its role in fostering inclusivity and collaborative decision-making. The paper finishes by underscoring the crucial significance of nurses in the domains of preventive nursing, health promotion, and community involvement. This highlights the need of adopting a comprehensive and interdisciplinary strategy to tackle the difficulties encountered by the healthcare system in Nigeria. The report promotes urgent and cooperative measures, emphasising the potential of the suggested ways to improve healthcare in Nigeria.